The Role of Pancreatic Enzyme Replacement Therapy in Unresectable Pancreatic Cancer: A Prospective Cohort Study. Issue 3 (March 2017) - Saito, Tomotaka; Hirano, Kenji; Isayama, Hiroyuki; Nakai, Yousuke; Saito, Kei; Umefune, Gyotane; Akiyama, Dai; Watanabe, Takeo; Takagi, Kaoru; Hamada, Tsuyoshi; Takahara, Naminatsu; Uchino, Rie; et al.
Abstract : Objectives: Although patients with pancreatic cancer (PC) are prone to exocrine pancreatic insufficiency, there are little evidence about pancreatic enzyme replacement therapy (PERT) in patients with PC, especially those receiving chemotherapy. Methods: This is a prospective consecutive observational study of PERT in patients with unresectable PC. We prospectively enrolled patients receiving chemotherapy for unresectable PC from April 2012 to February 2014 and prescribed oral pancrelipase of 48, 000 lipase units per meal (pancrelipase group). N-benzoyl-tryrosyl para-aminobenzoic acid test was performed at baseline. Patients receiving chemotherapy before April 2012 were retrospectively studied as a historical cohort. Data on the nutritional markers at baseline and 16 weeks were extracted, and serial changes, defined as the ratio of markers at 16 weeks/baseline, were compared between 2 groups. Results: A total of 91 patients (46 in the pancrelipase group and 45 in the historical cohort) were analyzed. N-benzoyl-tryrosyl para-aminobenzoic acid test was low in 94% of the pancrelipase group. Serial change in the pancrelipase group versus historical cohort was 1.01 versus 0.95 in body mass index ( P < 0.001) and 1.03 versus 0.97 in serum albumin ( P = 0.131). Conclusions: The rate of exocrine pancreatic insufficiency in unresectable PC was high, and PERT can potentially improve the nutritional status during chemotherapy.